Breeding eider ducks strongly influence subarctic coastal pond chemistry - Duda, Matthew P.; Hargan, Kathryn E.; Michelutti, Neal; Kimpe, Linda E.; Clyde, Nik; Gilchrist, H. Grant; Mallory, Mark L.; Blais, Jules M.; Smol, John (2019)
Arctic freshwater ponds are typically pristine and oligotrophic, however, seabird biovectors can markedly alter 29 water quality via enrichment with marine-derived nutrients and bioaccumulated metals. These ornithogenic inputs 30 can be the dominant factor structuring aquatic biota and the surrounding island flora. Here, we measured a suite 31 of limnological water chemistry variables and sediment geochemistry from 21 freshwater ponds influenced by 32 Common Eiders (Somateria mollissima) in Hudson Strait, near the northern communities of Cape Dorset (Nunavut) 33 and Ivujivik (Quebec). Nest counts and sedimentary δ15N values were used as proxies of bird abundance. Nutrient-34 rich guano from the nesting eiders visibly promoted the growth of catchment vegetation. Elevated metal (Al, Cd, 35 Zn), metalloid (Se), and nutrient concentrations (N, P) in the water of eider-affected sites were recorded (Sign test; 36 p = 0.004), but the proximity of many sites to the coast meant that variables related to ocean spray (conductivity, 37 Na+, Mg2+, Cl-, Sr) confounded the effects of birds on pond water chemistry. In contrast, sediment geochemistry 38 appeared to more clearly characterize sites according to the level of eider activity in their catchments by tracking 39 Pb, Cd, N, and P sedimentary concentrations (Sign test; p = 0.02). These results have direct implications for 40 reconstructing historical eider population trends using sediment archives, which is necessary to inform effective conservation management strategies. Environment and Climate Change Canada, W. Garfield Weston Foundation, Natural 49 Sciences and Engineering Research Council of Canada (NSERC), Pew Charitable Trusts, Nunavut General 50 Monitoring Plan (NGMP), ArcticNet Network Centres of Excellence Canada